Nalar Politik Kedaulatan Negara-Bangsa dalam Novel Layaly Turkistan karya Najib Al-Kailani: The Political Reason of The Sovereignty of The Nation State in The Novel "Layely Turkistan" by Najib Al-Kailani - Agus Sunarto; M. Hafidzulloh S.M (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This paper examines to understand the colonial politics that was carried out against the Turkistan people in Najib Al-Kailani's novel Nights in Turkistan through the framework of Giorgio Agamben's political philosophy. The main focus of this research with this perspective is trying to uncover the process of normalizing the colonial political paradigm, which consists of sovereign power, state of exception, bare life, and homo sacer. This research uses the descriptive qualitative method. This method is used because the data of this research is textual data consisting of words, sentences, paragraphs by the material object. The colonial practices carried out by the Chinese and Russians made the Turkistan nation experience a degradation of its existence from both social, political, and cultural aspects. Thus, this research will reveal more deeply the colonial process carried out by China and Russia than Giorgio Agamben's critique of political philosophy. The results of this study indicate that first, the practice of colonialism carries the consequences of sovereign power seeking legality as well as legal suspension of colony actions; second, the Turkistan peoples who were reduced and degraded in existence were vulnerable to colonial coercive action so that they did not have perfect accessibility.